HUBUNGAN ANTARA LITERASI MEDIA ONLINE DAN KINERJA PEMBELAJARAN DITINJAU DARI KEYAKINAN DIRI, MOTIVASI BELAJAR, DAN JENJANG SEMESTER MAHASISWA - Tabita Anggre Verossa; Laurentius Saptono (Jurnal Pendidikan Ekonomi dan Akuntansi, 2022)
This study aimed to determine: (1) the correlation between online media literacy and learning performance in term of self-confidence; (2) the correlation between online media literacy and learning performance in termof learning motivation; and (3) the correlation between online media literacy and learning performance in term of students’ semesters. This research was correlational study which was conducted from April to May 2021. The population of this research were active students of the Accounting Education Study Program, Faculty of Teacher Training and Education, Sanata Dharma University, totaling 204 students. The samples in this study amounted to 135 students who were taken by using proportional random sampling technique. The data were analyzed by product moment correlation. The results of this study indicated that: 1) there was a correlation between online media literacy and learning performance in student respondents with high self-confidence (Sig. (2-tailed) = 0,037), while there was no correlation between online media literacy and learning performance in student respondents with low self-confidence. (Sig. (2-tailed) = 0,095); 2) there was a correlation between online media literacy and learning performance in highly motivated student respondents (Sig. (2-tailed) = 0,038), while there was no relationship between online media literacy and learning performance in respondents low- motivated students (Sig.(2-tailed) = 0,488); and 3) there was a correlation between online media literacy and learning performance in high-semester student respondents (Sig. (2-tailed) = 0,014), while there was no correlation between online media literacy and learning performance in the lower semester tiered student respondents (Sig. (2-tailed) = 0,284).Keywords: Online media literacy, learning performance, self-confidence, learning motivation, and students’ semesters